A Low-Cost Uncooled Infrared Microbolometer by CMOS Process. (1st January 2015) - Shen, Ning; Huang, Zhengxing; Tang, ZhenAn
Abstract : This paper reports the implementation of a low-cost uncooled infrared microbolometer using a standard 0.5-μm CMOS process, in which the CMOS metal interconnect layers are used as the infrared sensitive material. The CMOS metal interconnect layers are Aluminum, with a TCR of 0.385%/K. Measurements show that the low-cost microbolometer has a thermal conductance of 1.95 × 10 −6 W/K, a thermal time of 3.69 ms, and a dc responsivity of 1536 V/W at 10-Hz chopper frequency. The total measured rms noise of the microbolometer was 0.537 μV for a 10-kHz bandwidth, resulting in a detectivity D * of 1.0 × 10 9 cmHz 1/2 /W.